Effect of Profitability, Financial Leverage, and Sales Growth on Financial Distress of Transportation and Logistics Sector Companies Listed on the Indonesia Stock Exchange 2020-2022 - Lia Nur Indah; Budi - Prasetya; Eva - Purnamasari (JOBS (Jurnal Of Business Studies), 2023)
The problem of financial distress experienced by transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) during the COVID-19 pandemic became a problem in this study. This study analyzed the effect of profitability, financial leverage, and sales growth on financial distress. Transportation and logistics sector companies listed on the IDX consecutively from 2020 to 2022 are the population in this study, where the total population is 26 companies. The census or saturated sample is the sampling method used in this study. The analysis of this study uses a logistic regression model processed with S.P.S.S. 25. This study shows that profitability and financial leverage significantly affect financial distress. Meanwhile, sales growth has no significant effect on financial distress